Effects of L-carnitine Supplementation in High-Fat Diet on Growth, Antioxidant Capacity and Lipid Metabolism of Golden Pompano (Trachinotus ovatus) - Chen, Xu; Niu, Jin; Wang, Jun; Zhao, Wei (Frontiers in Marine Science, 2022)
A 6-week feeding trial was carried out to investigate whether dietary L-carnitine supplementation could alleviate the adverse effects of high-fat diet on the growth, antioxidation and lipid metabolism of Trachinotus ovatus. Four isonitrogenous experimental diets were formulated supplementing with or without L-carnitine (low fat diet (D1): 13% lipid; high fat diet (D2): 20% lipid; D3: 20% lipid with 0.02% L-carnitine; D4: 20% lipid with 0.06% L-carnitine). The final body weight, weight gain rate, specific growth ratio and feed intake in fish fed with D2 diet were significantly lower than that of fish fed with D1, D3 and D4 diets (P < 0.05). The weight gain rate and specific growth ratio of D2 diet were as low as 167.21% and 2.41% initial body weight/d, respectively. However, experimental diets were unable to change the feed conversion ratio and survival rate of fish (P > 0.05). The lowest value of crude protein and the highest value of crude lipid of whole-body were found in fish fed with D2 diet (P < 0.05), which were 31.35% and 17.41% wet weight respectively. Meantime, the level of crude lipid of whole-body in fish fed with D3 and D4 diets was significantly higher than that of fish fed with D2 diet (P < 0.05). Besides, there were significantly higher levels of triglyceride and total cholesterol in the D2 diet when compared to the other diets (P < 0.05). Additionally, the superoxide dismutase activity, malondialdehyde content and the mRNA levels of manganese superoxide dismutase and glutathione peroxidase of the liver in fish fed with D2 diet were significantly higher than those fed with D1, D3 and D4 diets (P < 0.05). The mRNA levels of carnitine palmitoyl transferase 1 and peroxisome proliferator-activated receptors-alpha of the liver in fish fed with D2 diet were significantly higher than those fed with D1, D3 and D4 diets (P < 0.05). In conclusion, L-carnitine supplementation in high-fat diet improved the growth performance and health of T. ovatus by promoting lipid hydrolysis, improving cholesterol transport and antioxidant capacity. Therefore, we recommended the 0.02% addition level of L-carnitine for T. ovatus diet.